Uji Kadar Vitamin A Crackers Perlakuan Terbaik dari Proporsi Tepung Terigu: Ubi Jalar Kukus dan Penambahan Tepung Daun Kelor - Rahayu, Puji; Ernes, Atmiral; Sari, Poppy Diana (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 3 No 1 (2018)DO - 10.24843/JITPA.2018.v03.i01.p08, 2018)
Kelor (Moringa oleifera) is a type of herbaceous plants that are efficacious and a rich source of ?-carotene, protein, vitamin C, calcium, potassium and a good source of food as a natural antioxidant. Vitamin A cannot be provided by the body, so it must be met from the outside (essential). This study aims to determine the content of vitamin A in crackers of moringa leaves with the proportion of wheat flour: yellow steamed sweet potato : the right and most preferably organoleptic Moringa flour. This research uses a Quantitative Descriptive Design with 2 Factors. The proportion of wheat flour : steamed yellow sweet potato (90:10, 80:20, 70:30) as F1 and addition of moringa flour (3%, 6%, 9%) as F2 each treatment was repeated 3 times. The results of the research showed that the most preferred treatment was on the T2K1 treatment with the proportion of 80% wheat flour: 20% steamed sweet potato and 3% addition of moringa flour, obtained water content 2.04%, color preferences 5,7 (slightly like) preferences aroma 6.1 (rather like), taste level of taste 7.1 (like) and texture preferences 6.5 (like). The content of vitamin A in the best treatment of T2K1 was 23.66 mg / 100gr.